The role of artificial contact materials in experimental use-wear studies: A controlled proxy to understand use-wear polish formation. (February 2023) - Schunk, Lisa; Gneisinger, Walter; Calandra, Ivan; Marreiros, João
Highlights: Cutting movement on natural as well as on artificial contact material led to the development of use-wear traces. Hard contact material has more impact on the change in surfaces roughness compared to soft contact material. When the tool surface gets abraded, the surface does not necessarily get smoother; surface roughness can also increase. Both, tool use intensity/duration and tool raw material properties highly affect wear formation. The use of artificial contact material offers various advantages (ethical aspects etc.). Abstract: Traceological studies aim at the recognition and the identification of use-wear traces on artefacts to gain a functional interpretation of past human technologies. However, the development of use-wear traces is known to be dependent on different mechanics involved, such as those related to the contact materials, but also to the tool raw material and morphology, the use intensity and the performed task. Therefore, an understanding of the fundamental mechanics affecting wear formation is necessary to build reliable interpretations based on causation. The cause-effect relationship between individual variables and the formation of use-wear can only be investigated by conducting controlled, second-generation experiments. To test individual variables, others have to be standardised. This applies, for instance, to the contact material. The here presented sequential second-generation experiment tested for differences between soft and hard contact materials. Simultaneously, this experiment aimed to validate the comparability of artificial and natural contact material as a standardised substitute, but also as an ethically more acceptable choice. Combined with qualitative and quantitative use-wear analyses, the data generated throughout the experiment did not only provide insights into the development of use-wear, but also into abrasion processes within the experimental setup. Concerning these aspects, no significant difference between the natural and artificial contact materials could be observed. Consequently, while not used as direct proxies to interpret wear on archaeological artefacts, the use of standardised contact materials can be an advantageous choice in controlled experimental setups. Moreover, the experiment highlights the relevance of use intensity and duration in the context of wear formation.